2020
DOI: 10.3390/cancers12092655
|View full text |Cite
|
Sign up to set email alerts
|

FUCCI Real-Time Cell-Cycle Imaging as a Guide for Designing Improved Cancer Therapy: A Review of Innovative Strategies to Target Quiescent Chemo-Resistant Cancer Cells

Abstract: Progress in chemotherapy of solid cancer has been tragically slow due, in large part, to the chemoresistance of quiescent cancer cells in tumors. The fluorescence ubiquitination cell-cycle indicator (FUCCI) was developed in 2008 by Miyawaki et al., which color-codes the phases of the cell cycle in real-time. FUCCI utilizes genes linked to different color fluorescent reporters that are only expressed in specific phases of the cell cycle and can, thereby, image the phases of the cell cycle in real-time. Intravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…Quantitative and real-time tracking of the cell cycle dynamics is possible using the fluorescent ubiquitination-based cell cycle indicator 2 (FUCCI2). This tool developed by Miyawaki et al 22 , 23 , depicts with fluorescence the different phases of the cell cycle in real-time and is increasingly used to detect non-dividing cells in the context of cancer therapies 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative and real-time tracking of the cell cycle dynamics is possible using the fluorescent ubiquitination-based cell cycle indicator 2 (FUCCI2). This tool developed by Miyawaki et al 22 , 23 , depicts with fluorescence the different phases of the cell cycle in real-time and is increasingly used to detect non-dividing cells in the context of cancer therapies 24 .…”
Section: Introductionmentioning
confidence: 99%
“…FUCCI in vivo tumor imaging also demonstrated that conventional cytotoxic chemotherapy killed only proliferating cancer cells, and quiescent cancer cells were resistant to currently-used cytotoxic chemotherapy and restarted proliferation after cessation of chemotherapy [ 44 , 45 ]. This is one of the reasons why currently-used chemotherapy has limited efficacy against solid cancers [ 46 , 47 ]. OBP-301 was shown to decoy quiescent cancer cells within tumors to cycle with the decoyed tumors becoming sensitive to chemotherapy [ 40 ].…”
Section: Fluorescence Ubiquitination Cell Cycle Indicator (Fucci) mentioning
confidence: 99%
“…The above results showed that an oncolytic adenovirus can decoy quiescent cancer stem and non-stem cells, sensitize them to conventional chemotherapy, whereby they are killed by oncolysis and chemotherapy. FUCCI cell-cycle imaging guides the precise timing for chemotherapy to be administered to effectively eradicate the decoyed cancer cells [ 46 , 47 ] ( Figure 2 B).…”
Section: Fluorescence Ubiquitination Cell Cycle Indicator (Fucci) mentioning
confidence: 99%
“…RNA polymerase II is related to the cell cycle. Most of the cell cycle of cancer cells is static, and a few are dynamic [26,27]. Static cancer cells are the main obstacle to the treatment of cancer [28].…”
Section: Plos Onementioning
confidence: 99%